Challenges and Coping Strategies of Night Junior High School Learners in Learning Sequences and Series Through Mathematics in a Box - Amoto, Jeena A. (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aimed to explore the challenges and coping strategies of night junior high school learners in learning sequences and series through Mathematics in a Box. It involved a case study of a class of grade 10 Night Class learners in the Philippines. The principles of constructionism and symbolic interactionism backed up the thematic analysis of the data. During a six-week conversation, classroom observations and journal writing were done. Five learners participated in one-on-one interviews, and 10 in focus group interviews. Participants struggled with understanding, intricacy of rules, misconceptions, and with personal circumstances. Their coping strategies: dissecting the problem; speaking in a comfortable language; doing independent study; and reflecting on their answer. There is potential in using mathematics in a box to address challenges while learning sequences and series